2010
DOI: 10.1093/cid/ciq066
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Echocardiographic Abnormalities among HIV-infected Persons in the Era of Highly Active Antiretroviral Therapy

Abstract: in this large contemporary HIV cohort, the prevalence of subclinical functional and structural cardiac abnormalities was greater than expected for age. Abnormalities were mostly associated with expected and often modifiable risks. Lifestyle modification should become a greater priority in the management of chronic HIV disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
161
5
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(189 citation statements)
references
References 44 publications
17
161
5
2
Order By: Relevance
“…Although Mondy and colleagues did not find a significant association between HCV and PH, HIV-HCV coinfection was associated with left ventricular hypertrophy and left ventricular systolic dysfunction (24). In our study, the relationships between IFN treatment and echocardiographic outcomes persisted after adjustment for left atrial enlargement (although precision was poorer), echocardiographic diastolic Definition of abbreviations: ART = antiretroviral therapy; CI = confidence interval; HCV = hepatitis C virus; HIV = human immunodeficiency virus; IFN = interferon.…”
Section: Original Researchmentioning
confidence: 86%
See 1 more Smart Citation
“…Although Mondy and colleagues did not find a significant association between HCV and PH, HIV-HCV coinfection was associated with left ventricular hypertrophy and left ventricular systolic dysfunction (24). In our study, the relationships between IFN treatment and echocardiographic outcomes persisted after adjustment for left atrial enlargement (although precision was poorer), echocardiographic diastolic Definition of abbreviations: ART = antiretroviral therapy; CI = confidence interval; HCV = hepatitis C virus; HIV = human immunodeficiency virus; IFN = interferon.…”
Section: Original Researchmentioning
confidence: 86%
“…The Study to Understand the Natural History of HIV/AIDS in the Era of Effective Therapy (SUN Study) reported echocardiographic abnormalities in 656 HIV-infected patients, 84 (13%) of whom were coinfected with HCV (24). Although Mondy and colleagues did not find a significant association between HCV and PH, HIV-HCV coinfection was associated with left ventricular hypertrophy and left ventricular systolic dysfunction (24).…”
Section: Original Researchmentioning
confidence: 99%
“…7 Similar study on HIV positive subjects had shown the prevalence of 10 % with older age, diabetes and hypertension as the common risk factors. 8 Data regarding the burden of AIHD among hospital visiting patients and associated risk factors for IHD among them was not seen in literature.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 The presence of HIV/AIDS-associated comorbidity and co-infections have necessitated the concurrent use of SMX/TMP and antiretroviral medications containing LPV/r which have been shown to be of clinical benefits. 9 The concurrent use of LPV/r with SMX/TMP may possibly place more toxicological burden on the heart which pumps blood that serves as a means of drug transportation.…”
mentioning
confidence: 99%